Lithium oxalate lithium supplement agent, preparation method thereof and lithium battery

By using a combination of lithium oxalate, conductive agent and non-metal doped manganese dioxide in lithium batteries, combined with the spray drying process, the problem of excessive decomposition potential of lithium oxalate is solved, and the decomposition voltage is reduced and the performance is improved.

CN119627111APending Publication Date: 2025-03-14GANFENG LITHIUM CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411838571.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The actual decomposition potential of lithium oxalate in lithium batteries is too high, which limits its application as a positive electrode lithium supplement reagent.

Method used

The lithium oxalate supplementary agent is prepared by spray drying process by using a combination of lithium oxalate, conductive agent and non-metal doped manganese dioxide as catalysts, and the process parameters are adjusted to reduce the decomposition voltage of lithium oxalate.

Benefits of technology

It effectively reduces the actual decomposition voltage of lithium oxalate from 4.8V to 4.25V, while maintaining good integrity and wettability, making it suitable for applications as a cathode material for lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627111A_ABST
    Figure CN119627111A_ABST
Patent Text Reader

Abstract

The invention provides a lithium oxalate lithium supplement agent, a preparation method thereof and a lithium battery, and belongs to the technical field of lithium batteries. The lithium oxalate lithium supplement agent comprises lithium oxalate, a conductive agent and a catalyst, wherein the catalyst is nonmetal doped manganese dioxide. The lithium oxalate, the non-metal doped manganese dioxide and the conductive agent are mixed in water, and then spray drying is performed to obtain the lithium oxalate lithium supplement agent. The nonmetal doped manganese dioxide catalyst has a nano flower cluster shape and can be in close contact with lithium oxalate to form homogeneous microspheres, efficient solid-solid catalysis is promoted, the decomposition voltage of a lithium oxalate lithium supplement agent can be reduced to 4.25 V from 4.8 V, and meanwhile good integrity and wettability are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium oxalate lithium supplement and a preparation method thereof, and a lithium battery. Background Art

[0002] Pre-lithiation technology plays an important role in the development of lithium-ion batteries with high energy density and long cycle life. Different pre-lithiation technologies have their own advantages and disadvantages. 3 P.Li 2 S and Li 5 FeO 4 The positive electrode lithium replenishment reagents with materials such as lithium as the lithium source have the problem of reaction residues, which will significantly reduce the lithium replenishment capacity of the reagent. 3 P.Li 2 S and Li 5 FeO 4 The poor humid air stability of materials such as , limits their large-scale application. Therefore, low reaction residue, high lithium replenishment capacity and high humid air stability are the development direction of high-performance positive electrode lithium replenishment reagents.

[0003] Lithium oxalate (Li 2 C 2 O 4 ) is completely decomposed into carbon dioxide gas (CO 2 ), can be discharged from the battery system during the battery formation process to achieve a reaction without residue. This feature makes the theoretical lithium replenishment capacity of lithium oxalate comparable to that of metallic lithium. In addition, the water-stable property gives lithium oxalate high stability and high safety. At the same time, lithium oxalate (Li 2 C 2 O 4 ) has a theoretical decomposition potential as low as 3.0V, which meets the charge and discharge voltage range of conventional positive electrode materials. Therefore, the characteristics of no residue, high capacity and high stability make lithium oxalate an ideal lithium supplement reagent. However, the actual decomposition potential of lithium oxalate is as high as 4.7V, which seriously limits its application as a positive electrode lithium supplement reagent. Therefore, it is of great significance to study a lithium oxalate lithium supplement agent and a preparation method thereof for use in the positive electrode material of lithium batteries to reduce the actual decomposition voltage of lithium oxalate. Summary of the invention

[0004] The object of the present invention is to provide a lithium oxalate lithium supplement and a preparation method thereof and a lithium battery, so as to solve the problem of high actual decomposition potential of lithium oxalate in the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a lithium oxalate lithium supplement. The raw materials of the lithium oxalate lithium supplement include lithium oxalate, a conductive agent and a catalyst; the catalyst is non-metal-doped manganese dioxide.

[0007] Preferably, the preparation method of the non-metal-doped manganese dioxide is: potassium permanganate, manganese sulfate, and a non-metal additive are mixed in water for reaction to obtain the non-metal-doped manganese dioxide.

[0008] Preferably, the non-metallic additive comprises one or more of boric acid, carbon nanotubes and conductive carbon; the mass ratio of potassium permanganate, manganese sulfate and non-metallic additive is 0.2-0.6:0.04-0.08:0.1-0.3.

[0009] Preferably, the non-metallic additive is boric acid and / or carbon nanotubes.

[0010] Preferably, the reaction temperature is 70-90° C., and the reaction time is 2-6 hours.

[0011] Preferably, the mass ratio of the lithium oxalate, the conductive agent and the catalyst is 50-85:1-10:10-40.

[0012] Preferably, the conductive agent comprises one or more of Ketjen black, conductive carbon, carbon nanotubes and acetylene black.

[0013] The present invention also provides a method for preparing the lithium oxalate lithium supplement, comprising the following steps: mixing lithium oxalate, non-metal-doped manganese dioxide, and a conductive agent in water, and then spray-drying to obtain the lithium oxalate lithium supplement.

[0014] Preferably, the mass volume ratio of the lithium oxalate to water is 50-85 g:1000-1400 mL.

[0015] Preferably, the spray drying temperature is 230-260° C., and the flow rate is 2-10 mL / min.

[0016] The present invention also provides a lithium battery, wherein the positive electrode material of the lithium battery comprises the lithium oxalate lithium supplement agent described above.

[0017] Beneficial effects of the present invention:

[0018] (1) The non-metal-doped manganese dioxide catalyst of the present invention has a nano-flower cluster shape and can be in close contact with lithium oxalate to form homogeneous microspheres, thereby promoting efficient solid-solid catalysis.

[0019] (2) The decomposition voltage of the lithium oxalate supplement of the present invention can be reduced from 4.8 V to 4.25 V while maintaining good integrity and wettability.

[0020] (3) The present invention adopts a spray drying method to prepare the lithium oxalate supplement. By adjusting the process parameters, the particle size of the lithium oxalate supplement can be reduced, thereby achieving the purpose of reducing the decomposition voltage of lithium oxalate. The method for preparing the lithium oxalate supplement in the present application is simple, low-cost, and conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The XRD pattern of the non-metal-doped manganese dioxide prepared in Example 1;

[0022] Figure 2 This is a SEM image of the non-metal-doped manganese dioxide prepared in Example 1;

[0023] Figure 3 This is a SEM image of the boron-doped manganese dioxide prepared in Example 2;

[0024] Figure 4 This is a SEM image of carbon nanotube-doped manganese dioxide prepared in Example 3;

[0025] Figure 5 This is a SEM image of manganese dioxide prepared in Comparative Example 2;

[0026] Figure 6 This is a SEM image of the lithium oxalate lithium supplement prepared in Example 1;

[0027] Figure 7 This is the SEM image of the lithium oxalate lithium supplement prepared in Comparative Example 6. DETAILED DESCRIPTION

[0028] The present invention provides a lithium oxalate lithium supplement. The raw materials of the lithium oxalate lithium supplement include lithium oxalate, a conductive agent and a catalyst; the catalyst is non-metal-doped manganese dioxide.

[0029] In the present invention, the preparation method of the non-metal-doped manganese dioxide is: potassium permanganate, manganese sulfate and a non-metal additive are mixed in water for reaction to obtain the non-metal-doped manganese dioxide.

[0030] In the present invention, potassium permanganate, manganese sulfate and non-metal additives are mixed in water. Preferably, potassium permanganate and manganese sulfate are dissolved in water, and then the non-metal additives are added.

[0031] In the present invention, the non-metallic additive comprises one or more of boric acid, carbon nanotubes and conductive carbon; the mass ratio of potassium permanganate, manganese sulfate and non-metallic additive is 0.2-0.6:0.04-0.08:0.1-0.3, preferably 0.25-0.45:0.05-0.07:0.15-0.25, and further preferably 0.3-0.4:0.06-0.068:0.18-0.22.

[0032] In the present invention, the mass volume ratio of potassium permanganate to water is 0.2-0.6 g:60-100 mL, preferably 0.25-0.45 g:70-90 mL, and more preferably 0.3-0.4 g:80 mL.

[0033] In the present invention, the non-metal additive is boric acid and / or carbon nanotubes.

[0034] In the present invention, when the non-gold additives are boric acid and carbon nanotubes, the mass ratio of boric acid to carbon nanotubes is 0.002-0.005:0.15-0.25, preferably 0.003-0.004:0.18-0.22.

[0035] In the present invention, the reaction temperature is 70-90°C, preferably 75-85°C, more preferably 80°C, and the reaction time is 2-6h, preferably 3-5h, more preferably 3h, 4h, 5h.

[0036] In the present invention, after the reaction, the reaction product is preferably filtered, washed and dried to obtain non-metal-doped manganese dioxide.

[0037] In the present invention, the drying temperature is 120-180° C., preferably 130-170° C., more preferably 150-160° C., and the drying time is 1-6 h, preferably 2-5 h, more preferably 3-4 h.

[0038] In the present invention, the non-metal-doped manganese dioxide presents a nano-flower cluster shape, with a particle size of 10 to 50 nm and a specific surface area of ​​200 to 260 m 2 / g.

[0039] In the present invention, the mass ratio of the lithium oxalate, the conductive agent and the catalyst is 50-85:1-10:10-40, preferably 60-80:2-8:14-30, and more preferably 70-80:2-5:16-25.

[0040] In the present invention, the average decomposition voltage of the lithium oxalate lithium supplement is less than 4.5V, and the decomposition gram capacity is 350-520mAh / g.

[0041] In the present invention, the conductive agent comprises one or more of Ketjen black, conductive carbon, carbon nanotubes and acetylene black, preferably one or more of Ketjen black, conductive carbon and carbon nanotubes, and more preferably Ketjen black.

[0042] The present invention also provides a method for preparing the lithium oxalate lithium supplement, comprising the following steps: mixing lithium oxalate, non-metal-doped manganese dioxide, and a conductive agent in water, and then spray-drying to obtain the lithium oxalate lithium supplement.

[0043] In the present invention, the mass volume ratio of the lithium oxalate and water is 50-85 g:1000-1400 mL, preferably 60-80 g:1100-1300 mL, and more preferably 70-80 g:1200 mL.

[0044] In the present invention, the spray drying temperature is 230-260°C, preferably 230-250°C, more preferably 230-240°C, and the flow rate is 2-10 mL / min, preferably 3-8 mL / min, more preferably 4-6 mL / min.

[0045] The present invention also provides a lithium battery, wherein the positive electrode material of the lithium battery comprises the lithium oxalate lithium supplement agent described above.

[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0047] Example 1

[0048] Weigh 0.38g KMnO 4 and 0.068 g MnSO 4 ·H 2 O was added into 80 mL of deionized water and stirred for 10 min until it was completely dissolved to obtain a mixed solution; 0.0038 g of H 3 BO 3 and 0.2 g of carbon nanotubes were dispersed into the mixed solution, which was placed in a water bath at 80 ° C and stirred for 3 h. After the reaction, the slurry was filtered and washed, and finally dried at 150 ° C for 3 h to obtain non-metal-doped manganese dioxide with a particle size of 35.64 nm and a specific surface area of ​​238.46 m 2 / g.

[0049] 40 g of commercial lithium oxalate was weighed and dissolved in 600 mL of deionized water, and then 8 g of non-metal-doped manganese dioxide and 1 g of Ketjen black were added. After uniform dispersion, the mixture was spray-dried at a flow rate of 4 mL / min at 230 ° C to obtain a lithium oxalate supplement, recorded as LCO-1, with a gram capacity of 510.6 mAh / g.

[0050] Example 2

[0051] The difference from Example 1 is that no carbon nanotubes are added when preparing the non-metal-doped manganese dioxide, and the boron-doped manganese dioxide is obtained, and its particle size is 39.59 nm and the specific surface area is 207.06 m 2 / g, the obtained lithium oxalate lithium supplement was recorded as LCO-2, and the gram capacity was 478.6 mAh / g.

[0052] Example 3

[0053] The difference from Example 1 is that no H is added when preparing the non-metal-doped manganese dioxide. 3 BO 3 The carbon nanotube-doped manganese dioxide was obtained with a particle size of 106.64 nm and a specific surface area of ​​89.54 m 2 / g, the obtained lithium oxalate lithium supplement was recorded as LCO-3, and the gram capacity was 462.8mAh / g.

[0054] Comparative Example 1

[0055] 40 g of commercial lithium oxalate was weighed and dissolved in 600 mL of deionized water, and then 8 g of commercial manganese dioxide and 1 g of Ketjen black were added. After uniform dispersion, the mixture was spray-dried at a flow rate of 4 mL / min at 230° C. to obtain a lithium oxalate lithium supplement.

[0056] Comparative Example 2

[0057] Weigh 0.38g KMnO 4 and 0.068 g MnSO 4 ·H 2 O was put into 80 mL of deionized water and stirred for 10 min until it was completely dissolved to obtain a mixed solution, which was placed in a water bath at 80 ° C and stirred for 3 h. After the reaction, the slurry was filtered and washed, and finally dried at 150 ° C for 3 h to obtain manganese dioxide with a particle size of 159.32 nm and a specific surface area of ​​43.94 m 2 / g.

[0058] 40 g of commercial lithium oxalate was weighed and dissolved in 600 mL of deionized water, and then 8 g of manganese dioxide and 1 g of Ketjen black were added. After being evenly dispersed, the mixture was spray-dried at a flow rate of 4 mL / min at 230° C. to obtain a lithium oxalate lithium supplement.

[0059] Comparative Example 3

[0060] Weigh 0.38g KMnO 4 and 0.068 g MnSO 4 ·H 2 O was added into 80 mL of deionized water and stirred for 10 min until it was completely dissolved to obtain a mixed solution; 0.0038 g of H 3 BO 3 and 0.2 g of carbon nanotubes were dispersed in the mixed solution, which was placed in a water bath at 80° C. and stirred for reaction for 3 h. After the reaction, the slurry was filtered and washed, and finally dried at 150° C. for 3 h to obtain non-metal-doped manganese dioxide.

[0061] 40 g of lithium oxalate was weighed and dissolved in 600 mL of deionized water, and then 8 g of non-metal-doped manganese dioxide and 1 g of Ketjen black were added. The slurry obtained after uniform dispersion was sand-milled at a speed of 1500 rpm for 3 h. Finally, the sand-milled slurry was spray-dried at a flow rate of 4 mL / min at 230 ° C to obtain a lithium oxalate lithium supplement.

[0062] Comparative Example 4

[0063] The difference from Example 1 is that the spray drying temperature is 200° C., and other conditions are the same, to obtain a lithium oxalate lithium supplement.

[0064] Comparative Example 5

[0065] 40 g of lithium oxalate was weighed and dissolved in 600 mL of deionized water. After all the water was dissolved, the solution was spray-dried at a flow rate of 4 mL / min at 230° C. to obtain a lithium oxalate lithium supplement.

[0066] Comparative Example 6

[0067] Weigh 0.38g KMnO 4 and 0.068 g MnSO 4 ·H 2 O was added into 80 mL of deionized water and stirred for 10 min until it was completely dissolved to obtain a mixed solution; 0.0038 g of H 3 BO 3 and 0.2 g of carbon nanotubes were dispersed in the mixed solution, which was placed in a water bath at 80° C. and stirred for reaction for 3 h. After the reaction, the slurry was filtered and washed, and finally dried at 150° C. for 3 h to obtain non-metal-doped manganese dioxide.

[0068] 40 g of lithium oxalate, 8 g of non-metal-doped manganese dioxide and 1 g of Ketjen black were mixed, and then ball-milled at a rotation speed of 400 rpm for 3 h to obtain a lithium oxalate lithium supplement.

[0069] The performance tests were performed on the lithium oxalate lithium supplement agents of Examples 1 to 3 and Comparative Examples 1 to 6. The test method was as follows: a metal lithium sheet was used as the negative electrode, and the lithium oxalate lithium supplement agents of Examples 1 to 3 and Comparative Examples 1 to 6 were used to prepare the electrode sheets, and the button half-cells were assembled in a vacuum glove box with Celgand 2325 diaphragms. The assembled button half-cells were respectively subjected to performance tests. The test method was as follows: 0.1C charging to 4.8V, 0.1C discharging to 3.0V, and a standard capacity of 525mAh / g. The test results are shown in Table 1.

[0070] The method for preparing the pole piece using the lithium oxalate supplement of Examples 1 to 3 and Comparative Examples 1 to 6 is as follows: using N-methylpyrrolidone (NMP) as a solvent, the lithium oxalate supplement, acetylene black (ACET), a binder (PVDF) and a conductive agent (SP) are mixed in NMP at a weight ratio of 80:10:5:5, and after being mixed evenly, they are coated on both sides of an aluminum foil (the size of the aluminum foil is 18cm*7cm*12μm), PVDF is used in the form of a glue liquid, the solid content of the glue liquid is 20%, the thickness of the aluminum foil is 12μm, the purity is above 99%, and the unit mass of the pole piece is 0.6g / cm 2 .

[0071] Table 1 Test results of charging capacity and average charging voltage

[0072]

[0073]

[0074] It can be seen from Table 1 that the lithium oxalate supplement prepared by the present invention and added with non-metal-doped manganese dioxide has good electrical conductivity, which is beneficial to reducing the decomposition energy barrier of lithium oxalate.

[0075] Comparison between Example 1 and Example 2 shows that adding carbon nanotubes to manganese dioxide can further increase the conductivity of lithium oxalate and enhance its ability to reduce the reaction energy barrier.

[0076] By comparing Example 1 and Example 3, it can be seen that by doping with boron, non-metal-doped manganese dioxide with nano-flower clusters can be formed, which increases the specific surface area of ​​the catalyst, increases the contact area with lithium oxalate, and thus increases the gram capacity of the lithium oxalate lithium supplement.

[0077] Comparison between Example 1 and Comparative Example 3 shows that sand milling reduces the performance of the lithium oxalate lithium supplement. This is because the mechanical strength of sand milling is relatively large, causing the non-metal-doped manganese dioxide to be in an amorphous state, thereby affecting the catalytic effect.

[0078] From the comparison between Example 1 and Comparative Example 4, it can be seen that the spray drying temperature is too low, resulting in a higher water content in the lithium oxalate lithium supplement after spray drying, which further leads to a higher delithiation potential.

[0079] From the comparison between Example 1 and Comparative Example 5, it can be seen that the decomposition voltage of the lithium oxalate supplement prepared from lithium oxalate itself is relatively high.

[0080] From the comparison between Example 1 and Comparative Example 6, it can be seen that spray drying can promote the mixing of the catalyst and lithium oxalate in a "coated" form, and simple mechanical mixing cannot achieve the "coating" effect.

[0081] contrast Figure 2 , Figure 3 and Figure 4It can be seen that the effect of doping with boron element on the catalyst is obvious. The incorporation of boron is the key to the formation of nano-flower cluster catalysts. At the same time, the particle size and specific surface area of ​​the catalyst are significantly optimized, which is beneficial to increase the contact area between the catalyst and lithium oxalate, thereby reducing the decomposition voltage of lithium oxalate; and the catalyst synthesized by incorporating carbon nanotubes is agglomerated particles with a larger particle size and a specific surface area that is significantly inferior to the previous two, indicating that the presence of carbon nanotubes has little effect on the morphology of the catalyst, but combined with the test data, it can be seen that it can increase the conductivity of the catalyst.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lithium oxalate lithium supplement, characterized in that: The raw materials of the lithium oxalate lithium supplement include lithium oxalate, a conductive agent and a catalyst; the catalyst is non-metal-doped manganese dioxide.

2. The lithium oxalate lithium supplement according to claim 1, characterized in that: The preparation method of the non-metal-doped manganese dioxide is as follows: potassium permanganate, manganese sulfate and a non-metal additive are mixed in water for reaction to obtain the non-metal-doped manganese dioxide.

3. The lithium oxalate lithium supplement according to claim 2, characterized in that: The non-metallic additive comprises one or more of boric acid, carbon nanotubes and conductive carbon; the mass ratio of potassium permanganate, manganese sulfate and the non-metallic additive is 0.2-0.6:0.04-0.08:0.1-0.

3.

4. The lithium oxalate lithium supplement according to claim 3, characterized in that: The non-metal additive is boric acid and / or carbon nanotubes.

5. The lithium oxalate lithium supplement according to any one of claims 2 to 4, characterized in that: The reaction temperature is 70-90° C., and the reaction time is 2-6 hours.

6. The lithium oxalate lithium supplement according to claim 1, 2 or 4, characterized in that: The mass ratio of the lithium oxalate, the conductive agent and the catalyst is 50-85:1-10:10-40.

7. The lithium oxalate lithium supplement according to claim 6, characterized in that: The conductive agent comprises one or more of Ketjen black, conductive carbon, carbon nanotubes and acetylene black.

8. The method for preparing the lithium oxalate lithium supplement according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing lithium oxalate, non-metal-doped manganese dioxide and a conductive agent in water, and then spray-drying to obtain a lithium oxalate lithium supplement.

9. The method for preparing the lithium oxalate lithium supplement according to claim 8, characterized in that: The spray drying temperature is 230-260° C., and the flow rate is 2-10 mL / min.

10. A lithium battery, characterized in that: The positive electrode material contains the lithium oxalate lithium supplement agent according to any one of claims 1 to 7.

Citation Information

Cited By

  • Lithium supplement agent, preparation method thereof and battery

    CN120497342A

  • Nano lithium oxalate composite slurry as well as preparation method and application thereof

    CN122051189A

  • Composite nanometer organic lithium supplement agent, preparation method thereof and positive pole piece

    CN122158584A

  • Spherical lithium oxalate-catalyst composite lithium supplement agent as well as preparation method and application thereof

    CN122298418A